Time to first antenatal care contact and pooled prevalence among reproductive-age women in East Africa: Log-logistic shared frailty model - Simachew Getaneh Endalamew; Fetlework Gubena Arage; Asefa Adimasu Taddese; Dejen Kahsay Asgedom; Bewuketu Terefe; Solomon Keflie Assefa (PLoS ONE, 2025)
Background Antenatal care (ANC), the provision of prenatal healthcare by skilled medical practitioners, is essential for ensuring the well-being of pregnant women and their fetuses. It reduces maternal and child morbidity and mortality. However, there is a lack of comprehensive, region-wide analyses of ANC initiation, particularly across diverse East African countries. Therefore, this study aimed to determine the time to first antenatal care and its associated factors in East African countries. Methods Demographic and Health Survey (DHS) data from 2012–2022 consisting of 12 countries were extracted. A total of 93,213 weighted reproductive-age women (15–49 years) were included in this study. A Kaplan–Meier survivor curve was generated to estimate the time of the first antenatal care contact. A log-rank test was used to compare the difference in survival curves. The log-logistic gamma shared frailty model was selected based on the reduced Akaike and Bayesian Information Criteria, and Cox-Snell residual plot. The shared frailty model was utilized to capture the correlation of outcomes within clusters (countries), as individuals within the same country may experience similar risks. Results The pooled prevalence of women with a minimum of 4 ANC contacts in East African countries was 57.7% (95% CI: (49.9–65.1%). The variability in effect sizes of ANC utilization across included countries is estimated at τ2= 0.2032 [95% CI: 0.1111–0.6611]. The overall median time to the first antenatal care contact was 4 months. The log-logistic shared frailty model showed that place of residence [ϕ = 1.014, 95% CI: (1.006, 1.021)], maternal age [ϕ = 0.978, 95% CI: (0.970, 0.980)], women’s education level [ϕ = 0.964, 95% CI: (0.952, 0.971)], marital status [ϕ = 0.970, 95% CI: (0.963, 0.978)], wealth index [ϕ = 0.990, 95% CI: (0.982, 0.997)], healthcare distance [ϕ = 0.975, 95% CI: (0.969, 0.980)], and parity [ϕ = 1.111, 95% CI: (1.093, 1.129)] were significant determinants of time at first antenatal care visit. Conclusion Women in East Africa initiated their first ANC visit later than the optimal period recommended by the World Health Organization (WHO). The positive correlation between early ANC initiation and access to media, healthcare access, and educational attainment may be utilized to promote increased early engagement in ANC services. Thus, governments and other responsible bodies should strive to implement programs to enhance access to healthcare and education, particularly for women living in rural areas, to improve the early initiation of antenatal care visits.